If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 1x + 5 Reorder the terms: -3 + 2x = 1x + 5 Reorder the terms: -3 + 2x = 5 + 1x Solving -3 + 2x = 5 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 2x + -1x = 5 + 1x + -1x Combine like terms: 2x + -1x = 1x -3 + 1x = 5 + 1x + -1x Combine like terms: 1x + -1x = 0 -3 + 1x = 5 + 0 -3 + 1x = 5 Add '3' to each side of the equation. -3 + 3 + 1x = 5 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 5 + 3 1x = 5 + 3 Combine like terms: 5 + 3 = 8 1x = 8 Divide each side by '1'. x = 8 Simplifying x = 8
| 2(10x-3)=54 | | 4a-3(4-2a)= | | -0.4x=60 | | 1/42x-7/25 | | ln(x)=8.27 | | -3x+11=56 | | 23-4x-8+9x=-30 | | -2f+4(-2f+5)-3=17 | | 6x+12=20x-24 | | 10(4k+6t+3)= | | -1.5n-12=94 | | 4.4x-0.2=26.2 | | 0=7/2x-21/2 | | m/3=-27 | | 8x-31/6=x-5 | | y/18=64 | | (3x^2-4x)(2x^3+3x-1)=y | | 3(x-7)=(3x+2)(2x+1) | | 2u-u= | | p/3asfdr | | w/7.5=52 | | 5n=10-5n | | 3x(2x+7)= | | 9.8/1.4 | | 3/5-x | | 8s+7=9s | | 3(2z-10)=54 | | 4z-42=32-3 | | 2(7+11)+3(7)=57 | | 7x+x(x-5)=0 | | y-(-13)=4/3(x-(-11)) | | k/7=17 |